2017
DOI: 10.1124/jpet.117.244376
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Sulforaphane Produces Antinociception and Improves Morphine Effects during Inflammatory Pain in Mice

Abstract: The activation of nuclear factor erythroid 2-related factor 2 (Nrf2) exerts potent antioxidative and anti-inflammatory effects; however, its participation in the modulation of chronic inflammatory pain and on the antinociceptive effects of -opioid receptor (MOR) agonists has not been evaluated. We investigated whether the induction of Nrf2 could alleviate chronic inflammatory pain and augment the analgesic effects of morphine and mechanisms implicated. In male C57BL/6 mice with inflammatory pain induced by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 34 publications
5
57
0
Order By: Relevance
“…In this study, we found that SNI rats with anhedonia-like phenotype had lower tissue Keap1 and Nrf2 levels in the spinal cord than those in sham-operated rats. Given the role of Keap1-Nrf2 signaling in pain ( Kim et al, 2010 ; Redondo et al, 2017 ), reduced Keap1-Nrf2 signaling in the spinal cord may play a role in neuropathic pain, although not in anhedonia-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that SNI rats with anhedonia-like phenotype had lower tissue Keap1 and Nrf2 levels in the spinal cord than those in sham-operated rats. Given the role of Keap1-Nrf2 signaling in pain ( Kim et al, 2010 ; Redondo et al, 2017 ), reduced Keap1-Nrf2 signaling in the spinal cord may play a role in neuropathic pain, although not in anhedonia-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dietary intake of glucoraphanin during juvenile and adolescent stages confers resilience to chronic social defeat stress in adulthood ( Yao et al, 2016b ). Previous reports have shown that intrathecal administration of SFN attenuated mechanical allodynia and thermal hyperalgesia in spinal nerve transfection-injured mice ( Kim et al, 2010 ), and that SFN inhibited complete Freund’s adjuvant-induced allodynia and hyperalgesia ( Redondo et al, 2017 ). Taken together, it is likely that SFN is a potential natural compound for treating comorbid pain and depression.…”
Section: Introductionmentioning
confidence: 99%
“…In other experiments, the evaluation of the effects produced by the intraperitoneal injection of 10 mg/kg of SFN combined with 50 μg of morphine, subplantarly administered, on the allodynia and hyperalgesia induced by CCI was carried out at 3 h after SFN administration ( n = 6 animals per group). The doses of SFN and morphine were selected in accordance to other studies ( Redondo et al, 2017 ; Wang and Wang, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…SFN has been also proven in humans demonstrating that this treatment improves the glucose levels in patients with type 2 diabetes ( Axelsson et al, 2017 ), has beneficial clinical effects against autism disorders ( Singh et al, 2014 ) and gastrointestinal diseases ( Yanaka, 2018 ). Recent studies also showed the analgesic properties of SFN in several animal pain models and its capacity to potentiate the antinociceptive effects of opioids in animals with inflammatory pain or diabetic neuropathy ( McDonnell et al, 2017 ; Redondo et al, 2017 ). Taking account the lower efficacy of opioids, particularly μ-opioid receptor (MOR) agonists in the management of neuropathic pain ( Hervera et al, 2013 ; Zychowska et al, 2013 ; Popiolek-Barczyk and Mika, 2016 ), the investigation of new tools for increasing their analgesic efficacy is a priority in the current pain research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation